If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6x + -6) = 24 Reorder the terms: (-6 + 6x) = 24 Remove parenthesis around (-6 + 6x) -6 + 6x = 24 Solving -6 + 6x = 24 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 6x = 24 + 6 Combine like terms: -6 + 6 = 0 0 + 6x = 24 + 6 6x = 24 + 6 Combine like terms: 24 + 6 = 30 6x = 30 Divide each side by '6'. x = 5 Simplifying x = 5
| 2e^4x-2=2 | | 16-7y+14=3y+14-7 | | F-8=6+3f | | 2+r=2-7r | | 9.2+3.1=2.06+1.15x | | -7-7(-5n-5)=4(5n-7)-4 | | 49y=12(4y+12) | | w+-8=6 | | (2y+2)-(y+6)= | | 0=16t^2-300t+1000 | | 8(e-5)=2(3e-8) | | -1.5(-4.7)-4.7= | | 19-3n=-29 | | 14-x=-10 | | 3a+8=y | | -4j-2(3j+5)=-6j+2(j+2) | | 104=8(v+6) | | 4-3=2+8 | | 7x-750=5x-600 | | 3x-6(5+x)=-4(x+7) | | 6-6=9x+5x | | 2d+18=12-6(d+7) | | -1.5(-1.5)-4.7= | | -(-x)x=96 | | 10x=4x-28 | | 4.1(1-5.8v)=3.5v-14.996 | | -a+2b-8a= | | [2/3x-2/3]=2/3 | | 4j-2(3j+5)=-6j+2(j+2) | | -1.5x-1.5-4.7= | | 17y-13y=20 | | -3(x+2)+2(x+1)=2x+11 |